Demographic, Sociocultural, and Behavioral Predictors of Modern Contraceptive Uptake Among Couples in Northern Ghana - Allotey NK; Bosoka SA (Dove Medical Press, 2024)
Naa-Korkor Allotey,1,2 Samuel Adolf Bosoka3,4 1Ethics and Research Management Department, Research and Development Division, Ghana Health Service, Accra, Ghana; 2Department of Population, Family and Reproductive Health, School of Public Health, University of Ghana, Accra, Ghana; 3Disease Surveillance Unit, Volta Regional Health Directorate, Ghana Health Service, Ho, Ghana; 4Department of Epidemiology and Biostatistics, Fred N. Binka School of Public Health, University of Health and Allied Sciences, Ho, GhanaCorrespondence: Naa-Korkor Allotey, Email naa.korkorallotey@ghs.gov.gh; korkorallotey@gmail.comBackground: Despite efforts to increase modern contraceptive use in Ghana, prevalence rates remain low; particularly in Northern Ghana. This study, therefore, sought to determine the predictors of modern contraceptive use among couples in Northern Ghana. This research was the baseline assessment for a broader study aimed at determining the effect of an intervention to improve outcomes of modern contraception.Methods: The study was a cross-sectional design. Data was collected from 508 couples (1016 participants), using a multistage sampling technique; both members of each couple were interviewed separately. Univariate and stepwise multivariate logistic regression were used to identify predictors associated with modern contraceptive use. Qualitative data were analyzed to triangulate the findings from the quantitative data.Results: More than 97% of couples were Muslims. Qualitative data indicates that Muslims are less inclined to use Modern Contraceptives. Most participants had no education. The regression model shows that all demographic characteristics were not significant in Model 3 for men. Socio-culturally, men who gave the reason of "unconcerned" for men's non-involvement in contraceptive adoption, had less odds of using modern contraception (AOR=0.19). Men with high subjective norms were more than 15 times more likely to use modern contraception. Female farmers were less likely to use contraceptives (AOR= 0.45). Women who reported that "nothing prevented men" from getting involved in contraceptive adoption had greater odds of adopting modern contraception (AOR= 11.15). Women with good perceived behavioral control were more likely to use modern contraception (AOR=5.03). Women with high enacted stigma and men and women with high interspousal communication were more likely to adopt modern contraception.Conclusion: Taking cognizance of demographic and sociocultural characteristics and behavioral constructs is needed when determining the predictors of modern contraceptive use among couples in Northern Ghana.Keywords: predictors, modern contraceptive use, couples, demographic, sociocultural, behavioral, Northern Ghana